2020
DOI: 10.3390/app10072311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Assembly Error Effect on Stability Accuracy of Unmanned Aerial Vehicle Photoelectric Detection System

Abstract: A photoelectric detection system is a typical type of device widely used for detecting purposes based on unmanned aerial vehicles (UAV). Stability accuracy is the key performance index. Compared to traditional analysis methods aimed at unpredictable error-causing sources, assembly errors can be easily controlled during the manufacturing processes. In this research, an analysis method of assembly error effect on stability accuracy is proposed. First, by using kinematics analysis of homogeneous coordinate transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Based on our previous research of error modeling [31], the necessary predefinitions are shown as follows, and all modeling components are integrated together for the later analysis. Furthermore, because the device base is considered as being fixed to the UAV body, the dynamic modeling and related analysis of UAV can be simplified as that of the device base, which is presented as follows:…”
Section: Modeling and Simulations Of Uav Stability Precision And Error-causing Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous research of error modeling [31], the necessary predefinitions are shown as follows, and all modeling components are integrated together for the later analysis. Furthermore, because the device base is considered as being fixed to the UAV body, the dynamic modeling and related analysis of UAV can be simplified as that of the device base, which is presented as follows:…”
Section: Modeling and Simulations Of Uav Stability Precision And Error-causing Sourcesmentioning
confidence: 99%
“…The values of Δθ si are the differences between the ideal pointing positions and the real ones, and they are also defined as the pointing errors. The specific method to calculate Δθ si and RMS can be seen in our previous work [31] by using a series of statistic indexes (ii) The angular velocity of the device base related to the ground is denoted as ω ! p = ½δ px , 0, δ pz T , which can be measured by using high precision instruments [32], run-outs [33], including γ !…”
Section: Modeling and Simulations Of Uav Stability Precision And Error-causing Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the UAV assembly accuracy was comprehensively modeled and simulated using kinematic analysis of homogeneous coordinate transformation. en, by analyzing the manufacturing process, the shaft perpendicularity, runout, and assembly errors of the gyroscope were defined and modeled, which improved the photoelectric detection accuracy of the UAV [1]. By using drones, Escobar and Sandoval obtained 8,000 images with a spatial resolution of 1.40 cm on a 30-kilometer beach.…”
Section: Introductionmentioning
confidence: 99%